The Last Adam : a theology of the obedient life of Jesus in the Gospels - Crowe, Brandon D. (Grand Rapids : Baker Academic, 2017)
There is much discussion today about how we are to understand the life of Jesus in the Gospels. What was Jesus doing between his birth and death and how does this relate to salvation? The Last Adam considers the theological and soteriological significance of the life of Jesus in the Gospels from a primarily exegetical perspective. Brandon Crowe argues that Jesus is identified in the Gospels as the last Adam whose obedience recapitulates and overcomes the sin of the first Adam. Crowe shows that Jesus's obedience is presented by the Evangelists as the obedience of an anointed representative, which is counted vicariously on behalf of his people. Key topics covered include Jesus's baptism and temptation, his fulfillment of Scripture, the necessity of his works, the binding of the strong man and the inbreaking of the kingdom, and Jesus's death and resurrection. Crowe also discusses how his argument interfaces with systematic theology and the church's creedal traditions, which are often thought to say little about Jesus's life. Correcting the Christian tendency to minimize the life of Jesus, The Last Adam explains why the Gospels include much more than the Passion Narratives and shows that all four Gospels present Jesus's obedient life as having saving significance. - from publisher.
A tale of two Adams in the history of interpretation -- The last Adam and the Son of man in the Gospels -- The last Adam as the obedient Son of God -- The last Adam and the fulfillment of Scripture -- The glory of the last Adam in the Gospel of John -- The last Adam and the kingdom of righteousness -- The death and resurrection of the last Adam -- The last Adam and salvation : theological synthesis and Conclusions.
Includes bibliographical references and index.
Keywords: Jesus Christ -- Person and offices -- Biblical teaching; Adam -- (Biblical figure); Bible. -- Theology; Bible. -- Criticism, interpretation, etc; Typology (Theology)